Pilkada dan Peluang Fenomena Politik Dinasti di Wilayah Pemekaran: Studi Kasus Kabupaten Pesisir Barat - Lestari, Suci (Nakhoda: Jurnal Ilmu Pemerintahan, 2024)
The aim of this study is to examine the factors that contribute to the formation of dynasty politics in Pesisir Barat Regency through an in-depth analysis of the Pilkada process since 2013. A historical approach to political dynamics in this new region is relevant, especially regarding the potential for dynasty politics. Political network analysis techniques are applied to identify the relationships between the main political actors in the region, including potential candidates and other local political figures. The results of the study found that the incumbent AI has significant potential as an actor in the political dynasty movement in the 2024 Pilkada in Pesisir Barat Regency. The factors supporting the existence of the political dynasty are: (1) Regional Expansion; (2) Clientelism and Patronage; (3) Party Recruitment System; (4) Local Support; (5) Domino Coalition Effect; and (6) Limited Political Alternatives and Low Participation. The insights from this study have implications, especially in making the public and government aware that it is important to be more critical in choosing leaders by considering the track record and vision and mission of the candidates objectively. Active participation in elections and encouraging transparency in the party recruitment process are steps that can help prevent the dominance of dynastic politics and strengthen democracy at the local level.